Involvement of baroreflex deficiency in the age-related loss of estrogen efficacy against cerebral ischemia - Wang, Lei; Wang, Jia; Shan, Qing; Shu, He; Guo, Jin-Min (Frontiers in Aging Neuroscience, 2023)
For post-menopausal women, stroke is complicated by the discrepant outcomes of estrogen therapy as well as the therapeutic complications associated with advancing age. Estrogen therapy has been shown an age-dimorphic effect, which is neuroprotective in young females, but non-neuroprotective even neurotoxic in acyclic females. We hypothesized that arterial baroreflex and its down-stream acetylcholine-α7 nicotinic acetylcholine receptor (α7nAChR) anti-inflammatory pathway involve in the efficacy of estrogen toward cerebral ischemic damage. Our data showed that estrogen supplement contributed to arterial baroreflex improvement and neuroprotection in adult ovariectomy (OVX) rats but not in aged rats. In adult rats, estrogen deficiency induced by OVX aggravated middle cerebral artery occlusion (MCAO)-induced brain infarction and reduced arterial baroreflex function, with decreased α7nAChR expression of brain and exaggerated inflammatory following MCAO; these effects were significantly prevented by estrogen supplementation. Arterial baroreflex impairment by sinoaortic denervation partly attenuated the effect of estrogen on baroreflex sensitivity and ischemic damage in adult rats, as well as α7nAChR expression and inflammatory response. These data suggested that arterial baroreflex and acetylcholine-α7nAChR anti-inflammatory pathway involves in the neuroprotection of estrogen in adult OVX rats. In contrast, aged rats exhibited more severe ischemic damage and inflammatory response than adult rats, as well as poorer baroreflex function and lower α7nAChR expression. Estrogen supplement did not improve baroreflex sensitivity or confer neuroprotection in aged rats, without affecting brain α7nAChR and post-ischemic inflammatory. Most importantly, ketanserin restored the arterial baroreflex function and significantly postponed the onset of stroke in aged female stroke-prone spontaneously hypertensive rats, whereas estrogen treatment failed to delay stoke development. Our findings reveal that estrogen is protective against ischemic stroke in adult female rats, and arterial baroreflex is involved in the beneficial action; dysfunction of arterial baroreflex and unresponsiveness to estrogen in aged female rats may contribute to reduced estrogen efficacy against cerebral ischemia.